IPv6 mandates : choosing a transition strategy, preparing transition plans, and executing the migration of a network to IPv6 - Siil, Karl A. (Wiley, 2008)
"Ready or not, IPv6 is coming. While every enterprise will have some individual issues to manage, this guide will help you decide on a transition strategy, develop a plan, execute it, and verify progress. You'll understand the common tasks and recognize the risks and limitations of IPv6. Follow the guidelines, use the checklists, and you will find that making the transition is no longer intimidating; in fact, it may even require fewer resources than you anticipate."--Jacket